Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1056/nejmoa061760
|View full text |Cite
|
Sign up to set email alerts
|

Quadrivalent Vaccine against Human Papillomavirus to Prevent Anogenital Diseases

Abstract: The quadrivalent vaccine significantly reduced the incidence of HPV-associated anogenital diseases in young women. (ClinicalTrials.gov number, NCT00092521 [ClinicalTrials.gov].).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

24
1,084
3
79

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 1,674 publications
(1,209 citation statements)
references
References 28 publications
24
1,084
3
79
Order By: Relevance
“…12,13 Colposcopists were trained to locate and biopsy all discrete abnormal areas on the cervix. Women with CIN2, CIN3, or AIS (abbreviated as CIN2-3/AIS) or persistent CIN1 were referred for definitive therapy.…”
Section: Clinical Follow-up and Endpointsmentioning
confidence: 99%
See 3 more Smart Citations
“…12,13 Colposcopists were trained to locate and biopsy all discrete abnormal areas on the cervix. Women with CIN2, CIN3, or AIS (abbreviated as CIN2-3/AIS) or persistent CIN1 were referred for definitive therapy.…”
Section: Clinical Follow-up and Endpointsmentioning
confidence: 99%
“…Nonetheless, some women in the population for whom the vaccines are approved will have been exposed to vaccine HPV types through sexual activity before vaccination. 5,6 Though there have been extensive data published on the efficacy of both vaccines, [7][8][9][10][11][12][13][14][15] less is known about the impact of HPV vaccination in women with ongoing HPV16 or 18 infections. Adequate knowledge of the HPV vaccines' impact on such women has important clinical implications, particularly with respect to HPV16 and HPV18, as several studies have shown that women who are persistently or chronically infected with cervical HPV16 or HPV18 are at considerably higher risk for developing high grade cervical lesions and cancer, compared with women positive for non-HPV16/18 oncogenic types, oncogenic HPV-negative women, or those transiently infected with HPV16/18.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…While recognising the limitations of the still moderate (5 -6 years) follow-up in a few tens of thousand young women, two vaccines to date have shown high efficacy, safety, immunogenicity, long-term duration of protection and a strong suggestions of induction of immune memory (Harper et al, 2006;Garland et al, 2007;Paavonen et al, 2007; The Future II Study Group, 2007).…”
Section: Phase III Hpv Vaccination Trialsmentioning
confidence: 99%